Androgynous parents and guest children: The Huaorani Couvade - Rival, L (Blackwell Publishing, 1998)
Despite the current popularity of the post-feminist motto `gender is the effect of discourse, and sex the effect of gender' which defines sexuality as erotica and ignores its life-transmitting function, I argue that there can be no sound theorizing of sex and gender which does not account for procreative sex. I base my argument on a discussion of the way in which the Huaorani Indians of Amazonian Ecuador conceptualize human sexuality as the channel through which parenthood is created and intimate relationships formed. Childbirth rites (known in the literature as couvade) form an essential part of this process. Having reviewed past anthropological interpretations of the couvade and suggested some modifications to account for the androgynous nature of procreative life-giving in Amazonia, I show that social reproduction among the Huaorani is not primarily dependent on predation and warfare, but on the incorporation of the newborn. Returning in the Conclusion to postmodern views on sexuality, I highlight the limitation of analyses of subjective identity which do not address the beginning and perpetuation of life.